The Effect of Service Quality on Customer Satisfaction at Apeng Auto Service Workshop Using the Potential Gain in Customer Value Method - Naufal, Raffi Muhammad; Iriani, Iriani (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
Bengkel Apeng Auto Service operates as a provider of motor vehicle service, encompassing not only repairs but also offering oil changes and car washing services. Situated at Jl. Imam Bonjol no.7, Geluran, Taman District, Sidoarjo Regency, this establishment is equipped to address various mechanical and body-related issues in automobiles. Furthermore, it provides both new and used spare parts. This study employs a customer-centric potential gain approach to pinpoint attributes contributing to decreased customer satisfaction. Additionally, there exists one attribute with the lowest PGCV index, indicating satisfaction aligns with customer expectations; however, this doesn't rule out the potential for improvement, as evidenced by a PGCV index value of less than 10.5. The first attribute, E2 - Mechanic's Attention to Customer Preferences, holds a PGCV index of 10.46, while the second attribute, RE3 - Information about Product Sales to Customers, has a PGCV index of 10.27. It is advisable for Bengkel Apeng Auto to periodically assess their service quality to identify potentially dissatisfactory aspects from customers' perspectives. This practice enables the implementation of corrective measures to enhance customer satisfaction levels.